Normal physiological characteristics of elite swimmers - Wells, G.; Schneiderman-Walker, J.; Plyley, M. J. (Pediatric Exercise Science, 2006)
The purpose of this research was to develop a comprehensive normative database of the physiological characteristics of elite swimmers. Data were obtained from 195 elite swimmers (89 males and 106 females) ages 12 to 18 years. Six protocols were used to measure variables in the following categories: descriptive characteristics, cardiovascular, respiratory, strength and power, body composition, and anthropometry. Significant effects of gender and age were identified for a number of variables. These data could be used for the physiological assessment and talent identification of swimmers in comparison with other populations.